Hidden harmony: Converging interests in the development of prison reform - Mazur, Lucas B. (Theoretical criminology, 2021)
The “agonistic perspective” on criminal justice posits that tensions are ubiquitous in the field irrespective of time, place, and the given paradigm. While the study of conflict and contestation is important, it is equally necessary to study harmony and shared interests. In the present article, we explore a period in the history of European penal reform that was marked by such a convergence of interests, and which would in Poland wed institutional reactions to crime with pedagogy, rather than the field of law as seen in many other nations. Macro-level shifts following the First World War allowed for the convergence of three broad “currents” of the day: national penal reform; the field of pedagogy; and the self-ascribed social mission of the Polish intelligentsia. By taking seriously practical collaboration and ideological harmony we are also reminded that the (penal) systems of the West (particularly the USA and the UK) are not obvious, automatic, or necessary.